Matrix Computation / Second Edition - Jennings Alan; Mckeown J. J (John Wiley & Sons, 1992)
This book should appeal to engineers, scientists and numerical analysts, as well as graduate students and researchers in matrix computation. Preface, Basic Algebraic and Numerical Concepts, Some Matrix Problems, Computer Implementation, Elimination Methods for Linear Equations, Sparse Matrix Elimination, Some Matrix Eigenvalue Problems, Transformation Methods for Eigenvalue Problems, Sturm Sequence Methods, Vector Iterative Methods for Partial Eigen solution, Orthogonalization and Re-solution Techniques for Linear Equations, Iterative Methods for Linear Equations, Non-Linear Equations, Parallel and Vector Computing, Exercises, Bibliography, Appendices, Solutions to Exercises, Index.